Exposure of Nonbreeding Migratory Shorebirds to Cholinesterase Inhibiting Contaminants in the Western Hemisphere - Strum, Khara M.; Hooper, Michael J.; Johnson, Kevin A.; Lanctot, Richard B.; Zaccagnini, Maria Elena; Sandercock, Brett K. (Oxford Academic Press, 2019)
Migratory shorebirds frequently forage and roost in agricultural habitats, where they may be exposed to cholinesterase-inhibiting pesticides. Exposure to organophosphorus and carbamate compounds, common anti-cholinesterases, can cause sublethal effects, even death. To evaluate exposure of migratory shorebirds to organophosphorus and carbamates, we sampled birds stopping over during migration in North America and wintering in South America. We compared plasma Cholinesterase activities and body masses of individuals captured at sites with no known sources of organophosphorus or carbamates to those captured in agricultural areas where agrochemicals were recommended for control of crop pests. In South America, plasma acetylcholinesterase and butyrylcholinesterase activity in Buff-breasted Sandpipers was lower at agricultural sites than at reference sites, indicating exposure to organophosphorus and carbamates. Results of plasma Cholinesterase reactivation assays and foot-wash analyses were inconclusive. A meta-analysis of six species revealed no widespread effect of agricultural chemicals on Cholinesterase activity. However, four of six species were negative for acetylcholinesterase and one of six for butyrylcholinesterase, indicating negative effects of pesticides on Cholinesterase activity in a subset of shorebirds. Exposure to Cholinesterase inhibitors can decrease body mass, but comparisons between treatments and hemispheres suggest that agrochemicals did not affect migratory shorebirds' body mass. Our study, one of the first to estimate of shorebirds' exposure to cholinesterase-inhibiting pesticides, suggests that shorebirds are being exposed to cholinesterase-inhibiting pesticides at specific sites in the winter range but not at migratory stopover sites. Future research should examine potential behavioral effects of exposure and identify other potential sites and levels of exposure.